Anti-Inflammatory and Antiproliferative Properties of Sweet Cherry Phenolic-Rich Extracts - Gonçalves, Ana C. (2022)
Cherries have largely been investigated due to their high content in phenolics in order to fully explore their health-promoting properties. Therefore, this work aimed to assess, for the first time, the anti-inflammatory potential of phenolic-targeted fractions of the Saco cherry, using RAW 264.7 macrophages stimulated with lipopolysaccharide. Additionally, the cytotoxic effects on gastric adenocarcinoma (AGS), neuroblastoma (SH-SY5Y) and normal human dermal fibroblast (NHDF) cells were evaluated, as well as the ability to protect these cellular models against induced oxidative stress. The obtained data revealed that cherry fractions can interfere with cellular nitric oxide (NO) levels by capturing NO radicals and decreasing inducible nitric oxide synthase and cyclooxygenase-2 expression. Furthermore, it was observed that all cherry fractions exhibited dose-dependent cytotoxicity against AGS cells, presenting cytotoxic selectivity for these cancer cells when compared to SH-SY5Y and NHDF cells. Regarding their capacity to protect cancer cells against oxidative injury, in most assays, the total cherry extract was the most effective. Overall, this study reinforces the idea that sweet cherries can be incorporated into new pharmaceutical products, smart foods and nutraceuticals.